Temporal retinal thinning and the diagnosis of Alport syndrome and Thin basement membrane nephropathy. (4th March 2018) - Chen, Yan; Colville, Deb; Ierino, Francesco; Symons, Andrew; Savige, Judy
ABSTRACT: Background and objectives : Alport syndrome is an inherited disease characterized by renal failure, hearing loss, and ocular abnormalities, including temporal retinal thinning. This study compared retinal thinning in Alport syndrome and other renal diseases. Methods : Alport syndrome was diagnosed on renal biopsy and genetic testing. Subjects underwent optical coherence tomography (OCT) (Spectralis OCT, Heidelberg Instruments). Retinal thinning was determined from horizontal macular OCT scans through the foveal center using the formula: Temporal thickness index (TTI) = (nasal – temporal thickness) ÷ nasal thickness × 100%, and compared with the normal range for each age group. Statistical analysis was performed using Student's t test, Mann–Whitney U test, and ROC analysis (SPPS, IBM). Results : The mean temporal retinal thickness index was 12.4 ± 5.2% in men ( n  = 19) and 7.4 ± 1.4% in women ( n  = 28) with X-linked Alport syndrome; 13.1 ± 4.5% ( n  = 4) in recessive disease; 6.4 ± 2.2% ( n  = 5) in Thin basement membrane nephropathy; and 6.3 ± 3.3% ( n  = 14) in other renal diseases. Thinning was worse in men than women with X-linked disease ( p  < 0.01), and worse in men who developed early onset renal failure ( R 2  = 0.75). Temporal retinal thinning was 84% sensitive for men with X-linked Alport syndrome and 67% specific (AUC = 0.83) compared with other renal diseases. Conclusions : Retinal temporal thinning is diagnostic for X-linked Alport syndrome in men and distinguishes them this condition from Thin basement membrane nephropathy, but only in men ( p  = 0.002). Temporal retinal thinning may also identify men and women with the rarer autosomal recessive disease.